An assay that may predict the development of IgG enhancing allergen‐specific IgE binding during birch immunotherapy. Issue 9 (3rd September 2013) - Selb, R.; Eckl‐Dorna, J.; Vrtala, S.; Valenta, R.; Niederberger, V.
Abstract Background It has been shown that birch pollen immunotherapy can induce IgG antibodies which enhance IgE binding to Bet v 1. We aimed to develop a serological assay to predict the development of antibodies which enhance IgE binding to Bet v 1 during immunotherapy. Methods In 18 patients treated by Bet v 1‐fragment‐specific immunotherapy, the effects of IgG antibodies specific for the fragments on the binding of IgE antibodies to Bet v 1 were measured by ELISA. Blocking and possible enhancing effects on IgE binding were compared with skin sensitivity to Bet v 1 after treatment. Results We found that fragment‐specific IgG enhanced IgE binding to Bet v 1 in two patients who also showed an increase of skin sensitivity to Bet v 1. Conclusion Our results indicate that it may be possible to develop serological tests which predict the induction of unfavourable IgG antibodies enhancing the binding of IgE to Bet v 1 during immunotherapy.